SYNTHESIS, CHARACTERIZATION AND CYCLAZATION OF PYRAN USING Ag2O NANOPARTICLE FROM NATURAL SOURCE “GINGER” - D., Ruaa M.; Alsahib, S. A.; Ascar, I. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to synthesis Ag2O nanoparticles (N.P.s) utilizing the Ginger plant (Zingiber officinale) extract. As catalysts for pyran derivatives formation employing a three-component coupling reaction among aromatic and aliphatic aldehydes, malononitrile, and dimedone. The nanoparticles exhibit robust catalytic activity with high productivity. Results revealed that Ag2O NPs improved various vital features, like higher yields, reaction time, simple chemical separation, catalytic economic efficiency, and quick process. This study aimed to cyclize heterocyclic compounds to provide new hetero compounds applying nano-oxides obtained from natural (unmanufactured) sources and used in several medical, pharmaceutical, and industrial implementations. The outcomes nanoparticles were examined by Fourier Transform Infrared spectroscopy (FTIR) and transmission electron microscopy (T.E.M.); the chemical characteristics of the outcome compounds were tested by spectroscopy techniques (FTIR spectroscopy and 1H-NMR).